Znanstvene izdaje in elektronski medij Razprave - Ogrin, Matija (Studia litteraria, 2005)
The present volume of proceedings represents the first Slovenian book uniting well-nigh all the humanistic disciplines in a common task: to reflect on the role of scholarly editions in their own field. Moreover, it is the first to reflect systematically on the methodological and ecdotic issues of scholarly editions in the light of the possibilities opening with the electronic presentation of texts. While some humanistic disciplines in Slovenia boast a long tradition of scholarly editions, reaching back to the first half of the 19th century, others have begun to consolidate their editorial standards fairly recently.